Calculated k distribution coefficients for hydrogen- and self-broadened methane in the range 2000-9500 cm(-1) from exponential sum fitting to band-modelled spectra - Irwin, P; Calcutt, S; Taylor, F; Weir, A (1996)
The spectral band data derived by Strong et al. [1993] for laboratory-measured transmission spectra of hydrogen-broadened methane at 10 cm-1 resolution have been fitted with k coefficients over a wide range of pressures and temperatures representing those likely to be encountered in the atmosphere of Jupiter. The mean fitting error is found to be only 2.0×10-3 in transmission. These data are essential for the scattering calculations likely to be necessary for analysis of the data from the Near Infrared Mapping Spectrometer aboard the NASA Galileo spacecraft. The new data have significant advantages over those previously derived by Baines et al. [1993] in that they cover a wider spectral range, are applicable to longer paths, and also apply to the hydrogen-broadened case, which is the dominant broadening mechanism in this atmosphere. A similar table has also been calculated for the self-broadening case for comparison. Copyright 1996 by the American Geophysical Union.